Eutrophication evolution trajectory influenced by human activities and climate in the shallow Lake Gehu, China. (May 2022) - Zhang, Xiaoyu; Zhao, Jian; Ding, Lin; Li, Yuan; Liu, HaiXia; Zhao, YanFang; Fu, Guo
Graphical abstract: Highlights: The recovery trajectory of Lake Gehu is nonlinear and affected by many factors. Climate factors have offset the benefit of nutrient loads reduction. The algae production efficiency of total phosphorus affected Chl a significantly. The dynamic nutrient target has an important value for specific lake management. Abstract: Lake eutrophication has become a global environmental pollution problem. Analysis of the eutrophication recovery trajectory of lakes can help to accurately implement regulations and reduce the cost of management. The degradation and recovery trajectories of Lake Gehu were firstly analyzed based on 34-years monitoring data of water quality. A dynamic correlation analysis of the relationship between chlorophyll- a (Chl a ) and the total phosphorus (TP) (total nitrogen [TN]) at an annual scale was conducted using the filtering trajectory method (FTM). The result showed that the recovery trajectory of Lake Gehu was nonlinear, and showed a short lag time in Chl a decrease. The regime shift from a clear-water state to a turbid-water state occurred in Lake Gehu when the TP threshold was 120 μg/L. Combined the filtering trajectory diagram with a principal component analysis, the results revealed that the adverse climate change did not completely offset the positive effect of nutrient load reduction, which required further attention and had significance for eutrophication control. According to the dynamic changes in the algae production efficiency of total phosphorus (ETP), the result showed that the sensitivity of lake eutrophication increased and the TP carrying concentration reduced by 40%-60%. The water quality goal for controlling algae was determined as TP = 40 μg/L (Chl a  = 10 μg/L), which was 20% stricter than the national standard (TP = 50 μg/L). In conclusion, aquatic vegetation restoration and biological manipulation can be effective alternatives for controlling eutrophication in addition to nutrient load reduction. The eutrophication control target and adaptive strategies were determined according to the recovery trajectory of Lake Gehu in this study. The ETP has reference significance for the management of shallow lakes.